Test Bench for seal compression load testing. - Zhong Yang (131821) (2025)
The accuracy of calculating the reaction force in vehicle sealing systems using moment equilibrium equations from statics is highly dependent on the degree of simplification in the mathematical model. This study demonstrates that employing the Finite Element (FE) method allows for a comprehensive consideration of the coupling effects between the door and the flexible seal, thereby eliminating errors inherent to model simplification and single-boundary variables. Consequently, this approach improves the prediction accuracy of the sealing system’s reaction force. In this work, a multi-boundary coupling simulation method for a vehicle door sealing system was established using the Finite Element (FE) method, which accounts for the interaction between the seal and the complex door structure. The results, based on data from three distinct vehicle models (with three doors tested per model), show a mean absolute percentage error (MAPE) of 7% between the simulated and experimentally measured static closing forces. This close agreement verifies the reliability of the proposed method. This study provides a comprehensive strategy for predicting and optimizing the reaction force in vehicle sealing systems. It was found that a 75% increase in the compression load deflection (CLD) of the lock-side seal yields a 22% increase in the total sealing system reaction force.